β-adrenergic receptor regulates embryonic epithelial extensibility through actomyosin inhibition - Yohei Mizoguchi; Kaoru Nakashima; Ayato Sato; Asako Shindo (iScience, 2023)
Summary: During morphogenesis, epithelial tissues reshape and expand to cover the body and organs. The molecular mechanisms of this deformability remain elusive. Here, we investigate the role of the β-adrenergic receptor (ADRB) in orchestrating actomyosin contractility, pivotal for epithelial extensibility. Chemical screens on Xenopus laevis embryos pinpointed ADRB2 as a principal regulator. ADRB2 promotes actomyosin relaxation, facilitating apical cell area expansion during body elongation. In contrast, ADRB2 knockdown results in heightened cell contraction, marked by synchronous oscillation of F-actin and myosin, impeding body elongation. ADRB2 mutants with reduced affinity for ligand binding lack the function to induce cellular relaxation, highlighting the ligand’s essential roles even in the developing epidermis. Our findings unveil ADRB2’s critical contribution to extensibility of the epidermis and subsequent body elongation during development. This study also offers insights into the physiology of mature epithelial organs deformed by the smooth muscle response to the adrenergic autonomic nervous system.